Coronary artery spasm treated with intracoronary bioresorbable scaffold implantation under the guidance of treadmill test and optical coherence tomography: A case report - Yang Yang; Xinghua Jiang; Jun Guo; Kai Zou; Qianwei Huang; Biming Zhan (Annals of Noninvasive Electrocardiology, 2023)
Abstract Coronary artery spasm (CAS) can cause unstable angina, and the treatment of this disease is controversial. We report an elderly male patient who was admitted to hospital due to chest tightness. CAG showed that 70% stenosis in the middle of the right coronary artery (RCA). A bioresorbable scaffold (BRS) was implanted in the lesion under the guidance of optical coherence tomography (OCT). One year later, the patient's symptoms were relieved. The repeated CAG showed that the stent was good. BRS implantation under the guidance of treadmill test and OCT is one of treatment options for CAS patients.